Measuring the benefits of implementing asset management systems and tools - Mizusawa, Daisuke; McNeil, Sue (Midwest Regional University Transportation Center, 2008)
Although transportation agencies in the U.S. have been developing Asset Management Systems (AMS) for specific types of infrastructure assets, there are several barriers to the implementation of AMS. This paper documents the development of a generic methodology for quantifying the benefits derived from implementation of AMS and justifying investment in AMS implementation. The generic methodology involves three analysis methods: descriptive analysis, regression analysis, and benefit-cost analysis. This paper demonstrates how the methodology can be applied to evaluate the implementation of a pavement management system in terms of efficacy, effectiveness, and efficiency (3Es).
186 p.
Keywords: Regression analysis; Pavement management systems; Implementation; Economic benefits; Benefit cost analysis; Asset management